Status Hukum Wali Nikah bagi Ayah Pelaku Incest terhadap Anak Kandung: Tinjauan Empat Mazhab dan Kompilasi Hukum Islam - Fatah, Ahmad; Utami, Sri (Jurnal Penelitian, 2018)
The purpose of this study was to describe the legal status of the guardian of marriage for the father of the incest against the biological child. This study is limited to a review of four schools and the Compilation of Islamic Law (KHI). This study is a library research, which is to examine several basic and secondary references to discuss the subject matter of the study. The results of this study state that guardian marriage is one of the pillars of marriage and there is no marriage if there is no guardian. A marriage is considered invalid if there is no guardian who allows the bride to leave the bridegroom. Thus the presence of guardians in marriage can play a role in protecting women from possible disadvantages in their marital life. As for the marriage guardian, it is regulated in Article 19 to Article 23 Compilation of Islamic Law. Imam Maliki, Shafi'i, and Hambali argue that guardians are a legitimate condition of a marriage, while Imam Abu Hanifah argues that a woman may marry herself without a guardian. The legal basis of the opinions of Imam Maliki, Shafi'i, and Hambali are several hadiths. The opinion of Imam Abu Hanifah based on the hadith of the Prophet narrated by Bukhari and Muslim from Ibn Abbas r.a.